Foreign aid, terrorism and growth: Conditional evidence from quantile regression - Simplice Asongu; Jacinta C. Nwachukwu; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2018)
In this study, we investigate the role of development assistance in reducing a hypothetically negative impact of terrorism on economic growth, using a panel of 78 developing nations with data for the period 1984-2008. The empirical evidence is based on interactive Quantile regressions. Domestic, transnational, unclear and total terrorism dynamics are employed while development assistance measurements comprised: bilateral and multilateral aid variables. With regard to the investigated hypothesis, we consistently confirm that: (i) In quantiles where terrorism is found to increase (decrease) economic growth, its interaction with foreign aid decreases (increases) economic growth. (ii) Comparing thresholds of the modifying aid variables for which the hypothesis is either rejected or accepted reveals that higher levels of multilateral (bilateral) aid are needed to reverse the negative effect of total (unclear) terrorism on growth, than the quantity needed to reverse the positive impact of transnational (domestic and total) terrorism(s) on growth. (iii) There is scant evidence of positive net effects. Overall the findings broadly indicate that foreign aid is a necessary but not a sufficient policy tool for completely dampening the effects of terrorism on economic growth.
Keywords: C52; D74; F23; F35; O40; 330; Economic Growth; Foreign aid; Terrorism; Quantile regression